The physiological strain index modified for trained heat-acclimatized individuals in outdoor heat - Byrne, C.; Lee, J. K. W. (International Journal of Sports Physiology and Performance, 2019)
Purpose: To determine if the Physiological Strain Index (PSI), in original or modified form, can evaluate heat strain on a 0-10 scale, in trained and heat-acclimatized men undertaking a competitive half-marathon run in outdoor heat. Methods: Core (intestinal) temperature (TC) and heart rate (HR) were recorded continuously in 24 men (mean [SD] age = 26 [3] y, VO2peak = 59 [5] mL/kg·min). A total of 4 versions of the PSI were computed: original PSI with upper constraints of TC 39.5°C and HR 180 beats·min 1 (PSI39.5/180) and 3 modified versions of PSI with each having an age-predicted maximal HR constraint and graded TC constraints of 40.0°C (PSI40.0/PHRmax), 40.5°C (PSI40.5/PHRmax), and 41.0°C (PSI41.0/PHRmax). Results: In a warm (26.1-27.3°C) and humid (79-82%) environment, all runners finished the race asymptomatic in 107 (10) (91-137) min. Peak TC and HR were 39.7°C (0.5°C) (38.5-40.7°C) and 186 (6) (175-196) beats·min 1, respectively. In total, 63% exceeded TC 39.5°C, 71% exceeded HR 180 beats/min, and 50% exceeded both of the original PSI upper TC and HR constraints. The computed heat strain was significantly greater with PSI39.5/180 than all other methods (P < .003). PSI >10 was observed in 63% of runners with PSI39.5/180, 25% for PSI40.0/PHRmax, 8% for PSI40.5/PHRmax, and 0% for PSI41.0/PHRmax. Conclusions: The PSI was able to quantify heat strain on a 0-10 scale in trained and heat-acclimatized men undertaking a half-marathon race in outdoor heat, but only when the upper TC and HR constraints were modified to 41.0°C and age-predicted maximal HR, respectively.